A Grounded Theory Study of How Nurses Integrate Pregnancy and Full-Time Employment: Becoming Someone Different. Issue 3 (May 2016) - Quinn, Paul
Abstract : Background: A holistic exploration of the experience of how nurses integrate pregnancy and employment is lacking among the global nursing literature. Objective: The purpose of this research was to explore how primiparous U.S. nurses integrated pregnancy and full-time employment. Methods: Using a grounded theory approach, 20 nurses from the United States, who were pregnant and delivered their first baby—while employed full time on 12-hour work shifts—provided a firsthand account of how they incorporated pregnancy with professional nursing employment. Results: The basic social process, "becoming someone different, " emerged to explain how U.S. nurses integrated pregnancy and full-time employment in early and late stages. Four core categories were: (a) "looking different, feeling different, "(b) "expectations while expecting, " (c) "connecting differently, " and (d) "transitioning labor." Discussion: Within early and late stages, pregnant nurses becoming someone different navigate through various social interactions with peers and patients alike, with meaning assigned to those experiences. Research with pregnant nurses from other countries, nurses working in settings other than acute care, and multiparous nurses is needed to further expand on these findings.